2017
DOI: 10.1037/pag0000159
|View full text |Cite
|
Sign up to set email alerts
|

Sensory functioning and personality development among older adults.

Abstract: Deficits in sensory functioning, such as poor vision and hearing, take a significant toll on quality of life. Little is known, however, about their relation with personality development across adulthood. This study examined whether baseline and change in vision and hearing were associated with personality change over a four-year period. Participants (N= 7471; Mage= 66.89; 59% women) were drawn from the Health and Retirement Study. They provided data on vision, hearing, and personality both at baseline and four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
(67 reference statements)
2
8
0
Order By: Relevance
“…The largest predictor—self-reported health—is also intimately tied with changes in psychological characteristics (Takahashi et al., 2013; Wagner et al., 2016). Specifically, one perspective is that physical and sensory limitations lead to lifestyle changes and declines in energy, which may alter personality traits over time (Jokela et al., 2014; Stephan et al., 2016, 2017). The same may be true for character strengths.…”
Section: Discussionmentioning
confidence: 99%
“…The largest predictor—self-reported health—is also intimately tied with changes in psychological characteristics (Takahashi et al., 2013; Wagner et al., 2016). Specifically, one perspective is that physical and sensory limitations lead to lifestyle changes and declines in energy, which may alter personality traits over time (Jokela et al., 2014; Stephan et al., 2016, 2017). The same may be true for character strengths.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical tests of these conceptual considerations are rare. Using data from the Swedish OCTO study of people aged 80 and older, Berg and Johansson (2014) found little support for associations between visual acuity and late-life personality development, while Stephan, Sutin, Bosselut, and Terracciano (2017) reported that poor vision was indeed associated with steeper declines in extraversion and stronger increases in neuroticism. However, both of these studies were based on self-rated vision, leaving it an open question whether objectively assessed visual ability predicts late-life patterns of personality stability and change.…”
Section: Personality As An Antecedent and Buffer Of Late-life Functio...mentioning
confidence: 99%
“…It has previously been observed that reduced hearing capacity has a significant impact on the quality of life of the concerned persons [ 3 , 8 , 9 , 10 , 11 , 12 , 13 ]. Furthermore, uncorrected reduced hearing also influences all other persons who want to communicate with the impaired persons [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%